Carbon‐Based Capacitive Deionization Electrodes: Development Techniques and its Influence on Electrode Properties. Issue 4 (1st March 2021) - Angeles, Anne Therese; Lee, Jaeyoung
Abstract: Capacitive deionization (CDI) is a potential technology to provide cost efficient desalinated and/or softened water. Several efforts have been invested in the fabrication of CDI electrodes that not only has outstanding performance but also high chance of large scalability. In this personal account, the different techniques in developing carbon‐based materials are presented together with its actual effect on the surface and electrochemical properties of carbon. The categories presented are based on the studies done by the Electrochemical Reaction and Technology Laboratory, the Ertl Center, different research groups in South Korea, and selected papers from the past three years. Our perspective about research gaps and prospects are also included with the aim to increase interest for CDI research. Abstract : High performing carbon‐based materials are necessary to the progress of capacitive deionization. Researchers from the ERTL team and various groups from South Korea try to realize this by performing different material modifications. In this short review, we illustrate the different techniques chosen by these groups and its effect on the characteristics and performance of carbon.